Application of Grafted Silica Gel for Improvement of FAAS Conditions of Copper(II) Determination in Water Samples - Tobiasz, Anna; Walas, Stanisław; Buda, Marta; Laszczyk, Katarzyna; Trzewik, Bartosz; Mrowiec, Halina (Current Analytical Chemistry, 2014)
Silica gel was modified via silanization with 3-chloropropyltrimethoxysilane and subsequently Cu(II)-5- dodecylsalicylaldoxime was grafted. Obtained sorbent was applied to on-line copper(II) preconcentration and its FAAS determination. Effective copper(II) elution was observed for 2% v/v nitric acid. The new sorbent exhibits optimal sorption efficiency within pH 5.6 and 7.5. A portion of the sorbent may be used repeatedly for not less than 100 sorptiondesorption cycles. The sorbent indicates high sorption and elution effectiveness of ca. 96 and 99%, respectively. Introduction of a preconcentration step before flame atomic absorption spectrometry (FAAS) copper determination with 60 s loading time resulted in 12-fold increase in the measured absorbance. This could be further raised by extending the loading time. Metals, like Zn(II), Mn(II) and Pb(II) caused negative interference effect while presence of Ca(II) and Mg(II) caused increase in the obtained signals. Copper(II) in samples such as: well water, mineral water, river and tap water was determined via the standard addition method. Detection limit for the proposed procedure was estimated at 1.5 μg L-1 (3σ). Accuracy of the method was assessed via comparison of the results obtained for copper determination in ground water and waste water certificate reference materials with those obtained with the use of a reference method (ICP MS).
Keywords: salicylaldoxime